Use of systemic therapies in adults with atopic dermatitis: 12-month results from the European prospective observational study in patients eligible for systemic therapy for atopic dermatitis (EUROSTAD) - Marjolein de Bruin-Weller; Andrew E. Pink; Silvia M. Ferrucci; Annalisa Patrizi; Ake Svensson; Marie L. A. Schuttelaar; Marie Tauber; Marius Ardeleanu; Shyamalie Jayawardena; Moataz Daoud (Journal of Dermatological Treatment)
Background The European Prospective Observational Study in Patients Eligible for Systemic Therapy for Atopic Dermatitis (EUROSTAD) is an ongoing observational study aiming to describe characteristics of patients with atopic dermatitis (AD) treated with systemic therapy over time and the management of their disease in a real-world setting.Methods Data from patients enrolled in EUROSTAD between March 2017 and April 2019 were analyzed for systemic therapy use and treatment change over 12 months.Results 288 patients reported taking systemic medications; 42.7% received cyclosporine, 35.3% dupilumab, 28.1% methotrexate, 25.4% oral corticosteroids, 6.8% azathioprine, 6.1% injectable corticosteroids, and 3.4% mycophenolate. The median duration of treatment was 1.1 months for oral systemic corticosteroids, 3.2 months for injectable corticosteroids, 4.8 months for cyclosporine, 7.3 months for methotrexate, and 14.9 months for dupilumab. The most frequent reasons for stopping treatment included lack of efficacy, patient decision, adverse events, and disease well controlled.Conclusion The 12-month interim EUROSTAD study analysis highlights the current trends and outcomes of systemic treatments for moderate-to-severe AD. Among all systemic treatments for AD, dupilumab was the least likely to be discontinued, whereas cyclosporine and corticosteroids, whilst effective, were primarily limited to episodic flare management consistent with treatment guidelines.